Experimental orthotopic implantation of tissue-engineered tracheal graft created based on devitalized scaffold seeded with mesenchymal and epithelial cells - M. V. Balyasin; D. S. Baranovsky; A. G. Demchenko; A. L. Fayzullin; O. A. Krasilnikova; I. D. Klabukov; M. E. Krasheninnikov; A. V. Lyundup; V. D. Parshin (Вестник трансплантологии и искусственных органов, 2020)
Objective: to study the viability of a tissue-engineered graft (TEG) based on a devitalized tracheal scaffold (DTS) seeded with mesenchymal stromal and epithelial cells in an experiment on rabbits with assessment of cytocompatibility and biocompatibility in vivo. Materials and methods. Syngeneic mesenchymal stromal bone marrow cells (MSBMCs) and syngeneic lung epithelial cells of rabbit were obtained. The morphology and phenotype of the MSBMC culture were confirmed via immunofluorescence staining for CD90 and CD271 markers. Pulmonary epithelial cells obtained by enzymatic treatment of minced rabbit lung tissue were stained with CKPan, CK8/18 and CK14 markers characteristic of epithelial cells. The donor trachea was devitalized in three successive freezethawing cycles. Double-layer cell seeding of DTS was performed under static and dynamic culturing. Orthotopic implantation of TEGs was performed at the site of the anterolateral wall defect in the rabbit that was formed as a result of tracheal resection over four rings. Results were evaluated by computed tomography, histological and immunohistochemical analyzes. Results. A TEG implant, based on DTS, with bilayer colonization by cell cultures of rabbit MSBMC and epithelial cells was obtained. Three months after implantation, TEG engraftment was noted, no tracheal wall stenosis was observed. However, slight narrowing of the lumen in the implantation site was noted. Six months after implantation, viability of TEG was confirmed by histological method. Epithelialization and vascularization of the tracheal wall, absence of signs of purulent inflammation and aseptic necrosis were shown. The small narrowing of the lumen of trachea was found to have been caused by chronic inflammation due to irritation of the mucous membrane with suture material. Conclusion. A new model for assessing the viability of a tissue engineering implant when closing a critical airway defect was created. The developed TEG – based on DTS seeded (bilayer) by lung epithelial cells and BMSCs – was successfully used to replace non-extended tracheal defects in an in vivo experiment. The use of tracheal tissue-engineered graft for orthotopic implantation showed biocompatibility with minimal tissue response.